La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.